Avoiding the oxidation of SiC in SiC-borosilicate glass composites by adding zinc. (January 2015) - Cheng, Xiaozhe; Wang, Yanhui; Liang, Yaqing; Zang, Jianbing; Lu, Jing; Yu, Yiqing; Xu, Xipeng
Highlights: Oxidation of SiC was inhibited by the preferential oxidation of Zn. The oxidation resultant of Zn could enter into the glass network. 6 wt.% Zn additive was enough for inhibiting the oxidation of SiC. When the Zn content was 8 wt.%, the oxidation resultant of Zn formed willemite. The formed willemite decreased the bending strength of the composites. Abstract: The oxidation of SiC in SiC-borosilicate glass composites during sintering produces gases, which causes high volume expansion and limits application of the composites in packaging fields. In this study, Zn was added into the composites and SiC was protected by the preferential oxidation of Zn. As Zn was over 6 wt.%, the oxidation resultant of Zn formed gahnite and willemite. Willemite caused thermal stress and decreased the bending strength. The composites with 6 wt.% Zn got minimum volume expansion ratio (−2.3%) and maximum bending strength (75.4 MPa), by contrast, that of the composites without Zn was 36.5% and 16.6 MPa.